Impact Analysis of Millennial Financial Literacy and Digital Ecosystem Collaboration on Operational Efficiency and Financial Performance of Start-ups in Jakarta - Nampira, Ardi Azhar; Apriyanto, Apriyanto; Arisondha, Edy (Westscience Press, 2025)
This study investigates the impact of Millennial Financial Literacy and Digital Ecosystem Collaboration on Operational Efficiency and Financial Performance in Jakarta-based startups. Using quantitative analysis with 180 samples and Structural Equation Modeling - Partial Least Squares (SEM-PLS), the research identifies significant positive relationships among the variables. Millennial Financial Literacy enhances decision-making and resource allocation, driving operational efficiency and financial performance. Digital Ecosystem Collaboration is shown to have the strongest effect on operational efficiency and financial performance, emphasizing its role in fostering innovation and efficiency. The findings highlight operational efficiency as a critical mediator, bridging financial literacy, collaboration, and financial outcomes. Practical implications include fostering financial education and leveraging ecosystem partnerships for startups to achieve holistic growth. These results contribute to the literature on digital entrepreneurship and provide actionable insights for startup managers.